Blue-emitting single band ratiometric luminescent thermometry based on LaF3:Pr3+. (18th June 2021) - Stefanska, Joanna; Maciejewska, Kamila; Marciniak, Lukasz
Abstract : Blue-emitting single band ratiometric luminescent thermometer based on Pr 3+ emission. Abstract : In accordance with the growing popularity of luminescence thermometry in the single-band-ratiometric approach configuration, we developed the first blue-emitting case based on LaF3 :Pr 3+ . By using excitations matched to ground- and excited-state absorption, strong thermally activated quenching and enhancement of the band associated with the 3 P0 → 3 H4 electronic transition were obtained, respectively. Due to the differences in the thermal dependences of the luminescence intensity signals for different Pr 3+ concentrations being controlled by the thermally activated cross-relaxation depopulation process, independencies of the calibration curves for the Pr 3+ content were obtained. Concentration-independent high relative sensitivities of the temperature reading, reaching even 5–6% K −1 with 0.5 K temperature determination uncertainty, confirm the high applicative potential of the developed blue-emitting Pr 3+ ion-based luminescent thermometer.